Ambient assisted living Italian forum 2019 - Monteriù, Andrea; Freddi, Alessandro; Longhi, Sauro (Springer, 2021)
This book documents the state of the art in the field of ambient assisted living (AAL), highlighting technologies and services which aim to improve health and quality of life, while promoting active aging. The coverage is wide ranging, with topical sections devoted to human monitoring, smart living services, biomedical and robotic solutions, including different case studies and real-world examples where assistive technologies are successfully applied. The book comprises a selection of the best, refereed papers presented at the 10th Italian Forum on Ambient Assisted Living (ForItAAL), held in Ancona, Italy, in June 2019, which represents the annual event that involves the Ambient Assisted Living Italian Association and brought together researchers, technology teams, policy makers, and stake-holders. Readers will find that the expert contributions offer clear insights into the ways in which the most recent exciting advances may be expected to assist in addressing the needs of the elderly and those with chronic conditions.